Comparative Analysis of Healthcare System, Financial, and Governance Developments Pre- and Post-Covid-19: Lessons Learned and Future Directions - Yaseen, Abid; Nawaz, Ali; Zhaira, Dua (Journal of Neonatal Surgery, 2025)
Background: The COVID-19 pandemic exposed critical vulnerabilities in Pakistan’s health system ranging from fragmented service delivery and inadequate financing to governance deficiencies. Before the pandemic, health expenditure stagnated near 1.4% of GDP, with heavy reliance on out-of pocket payments and stark disparities across regions¹. Objective: This study aims to compare Pakistan’s healthcare system performance, financial resilience, and governance mechanisms before and after COVID-19, drawing lessons for building a more equitable and crisis-prepared health architecture. Methods: Adopting a comparative descriptive-analytical design, the study synthesizes data from peer-reviewed publications, government reports, WHO and World Bank databases, and national health ministry documents (2010–2024). Thematic domains service delivery, health financing, and governance reforms—were analyzed through descriptive statistics and qualitative synthesis, with triangulation across sources ensuring robustness. Results: Pre-COVID-19, Pakistan’s primary healthcare (PHC) was underdeveloped, health spending was insufficient, and coordination between federal and provincial entities was limited. The pandemic, however, accelerated PHC reprioritization, revealed fiscal inflexibilities with continued high catastrophic OOP burdens², and catalyzed governance innovations like the National Command and Operation Center (NCOC), enabling data-driven, multi-sector coordination³. Conclusion: COVID-19 revealed systemic frailties yet provided a window for reform. Sustaining these gains requires embedding crisis governance mechanisms into routine public health frameworks, investing in financial protection, and ensuring resilient service delivery.